2014
DOI: 10.1044/2014_lshss-13-0032
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Plural Morphology in Children Acquiring /S/-Leniting Dialects of Spanish

Abstract: Assessments of plural morphology as a clinical marker of language impairment in Spanish-speaking children may be problematic, especially in children acquiring dialects of Spanish with /s/ lenition, such as those originating in Chile, the Dominican Republic, Cuba, Puerto Rico, and Central America. Instead, for children acquiring /s/-leniting dialects of Spanish, assessments of the plural marker in noun phrases produced within a sentence frame may be a better indicator of acquisition than traditional Berko-style… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…On the other hand, it is possible that children's comprehension mirrors their production in that they neither produce nor comprehend one of the variant forms at the earlier stages in development. Thus far, comprehension studies of natural language support the latter view, that is, children's reliance on only one form rather than two in language production is mirrored by their comprehension of one form, but not the other (e.g., Davies et al, 2019;Miller, 2014). For example, Miller and Schmitt (2012) found that children acquiring varieties of Spanish where /-s/ is variably omitted took longer to associate plural /-s/ to a more-than-one interpretation in comprehension as compared to children acquiring dialects of Spanish in which the plural marker is more consistently produced (see also Lukyanenko & Miller, 2019;Miller, 2007Miller, , 2014.…”
Section: Production Vs Comprehensionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it is possible that children's comprehension mirrors their production in that they neither produce nor comprehend one of the variant forms at the earlier stages in development. Thus far, comprehension studies of natural language support the latter view, that is, children's reliance on only one form rather than two in language production is mirrored by their comprehension of one form, but not the other (e.g., Davies et al, 2019;Miller, 2014). For example, Miller and Schmitt (2012) found that children acquiring varieties of Spanish where /-s/ is variably omitted took longer to associate plural /-s/ to a more-than-one interpretation in comprehension as compared to children acquiring dialects of Spanish in which the plural marker is more consistently produced (see also Lukyanenko & Miller, 2019;Miller, 2007Miller, , 2014.…”
Section: Production Vs Comprehensionmentioning
confidence: 99%
“…Thus far, comprehension studies of natural language support the latter view, that is, children's reliance on only one form rather than two in language production is mirrored by their comprehension of one form, but not the other (e.g., Davies et al, 2019;Miller, 2014). For example, Miller and Schmitt (2012) found that children acquiring varieties of Spanish where /-s/ is variably omitted took longer to associate plural /-s/ to a more-than-one interpretation in comprehension as compared to children acquiring dialects of Spanish in which the plural marker is more consistently produced (see also Lukyanenko & Miller, 2019;Miller, 2007Miller, , 2014. Similarly, children acquiring African American English tend not only to omit third person singular -s (e.g., Newkirk-Turner & Green, 2016), but also do not comprehend it (De Villiers & Johnson, 2007).…”
Section: Production Vs Comprehensionmentioning
confidence: 99%
“…We concentrate on accuracy in gender agreement because more data are available, and bilingual effects have clearly been established. Furthermore, across Spanish dialects final /s/ lenition varies widely, which impacts timing of acquisition of grammatical number (Miller, 2014). Such variability renders reliable comparisons across the research literature less reliable.…”
Section: Introductionmentioning
confidence: 99%
“…Goldstein and Iglesias (2001) show that accounting for dialect consonantal differences significantly influences results in both SLI and typically developing (TD) children. Likewise, Miller (2014) found that her results for children without SLI speakers of -s lenition dialects were similar to those of bilingual Mexican-dialect speakers in the United States with SLI in Bedore and Leonard (2001).…”
Section: Sli and Incipient Bilingualsmentioning
confidence: 63%